Preparation method and application of column [5] arene conjugated polymer containing D-A-D structure
By designing a columnar aromatic conjugated polymer with a DAD structure [5] and copolymerizing it with a triphenylamine derivative, the problems of complex synthesis and insufficient performance of conjugated polymer electrochromic materials were solved, achieving a fast response and high optical contrast electrochromic effect, which is suitable for dimming glass and smart portholes.
Patent Information
- Application Number
- CN202511365446.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2025-12-05
AI Technical Summary
Existing conjugated polymer electrochromic materials suffer from problems such as complex synthesis, high cost, low charge transport efficiency, slow response, and low optical contrast. In particular, in electrochromic devices, the obstruction of ion transport leads to poor performance.
A columnar[5]arene conjugated polymer with DAD structure was prepared by copolymerizing columnar[5]arene with rigid macrocyclic structure with triphenylamine derivative containing DAD structure, thereby improving the diffusion rate of electrolyte between conductive polymers.
It achieves faster color-changing response time, greater optical contrast and better cycle stability, with tinting response time of 1.25s and fading response time of 2.26s, respectively, and optical contrast improved to 53.12%, making it suitable for fields such as dimming glass and smart portholes.
Smart Images

Figure CN121064449A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of high polymer materials and electrochromic technology, and in particular to a preparation method and application of a column [5] arene conjugated polymer containing a D-A-D structure. BACKGROUND
[0002] Electrochromism refers to the phenomenon that, under the action of an applied voltage, due to the embedding and de-embedding of electric charges, an electrochromic material can undergo an electrochemical redox reaction, the optical absorption in the visible-near infrared region changes, and macroscopically, the color and transmittance change reversibly. At present, electrochromic materials have been applied in the fields of intelligent porthole of aircraft, anti-dazzling rearview mirror, and dimmable glass.
[0003] Compared with inorganic materials and small organic molecules, conjugated polymers have significant advantages: better optical memory effect, stable redox pairs, easy modification, and easy processing into films. However, despite these advantages, the development of conjugated polymer electrochromic materials still faces many challenges: ① Traditional molecular design relies on complex multi-step synthesis, resulting in high cost and complex process. The charge transport efficiency and electrochemical stability of some polymers still need to be improved. ② The preparation of conjugated polymers mostly uses electrochemical polymerization method, which involves disordered polymerization between monomers, making it difficult to study the relationship between structure and performance. ③ The electro-polymer is closely packed, and the diffusion speed of electrolyte between conductive polymers is slow, requiring longer embedding and de-embedding time, resulting in poor performance of electrochromic devices. For example, in the work of Jun Kawahara et al., in order to prepare a stable and water-treatable polymer system, they chemically doped poly(3,4-ethylenedioxythiophene) (PEDOT) with polystyrene sulfonic acid (PSS) to obtain a new chemical material system PEDOT:PSS, and applied it in the field of electrochromic. However, this material has slow switching response (both bleaching and coloring takes several seconds or even tens of seconds) and low optical contrast (less than 30%). According to the AFM structure of this material, it is found that this material presents a dense film morphology. Combined with the electrochromic principle of conductive polymers, it is inferred that the slow switching response and low optical contrast of this material are due to the dense film morphology which hinders ion transport to a large extent (A poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) / titanium oxide nanocomposite film synthesized by sol–gel assisted electropolymerization for electrochromic application / Thin Solid Films 584(2015)353–358 / DOI:http: / / dx.doi.org / 10.1016 / j.tsf.2014.12.008).
[0004] How to achieve wide color gamut, high coloring efficiency, fast response and excellent stability at the same time through simple and efficient molecular design strategy is still a key challenge in the field of electrochromic materials, and new construction strategies and methods of electrochromic polymers are urgently needed.
[0005] The introduction of supramolecular chemistry opens up new paths for the design and functionalization of conjugated polymers. Pillararenes are a kind of macrocyclic compounds with an electron-rich cavity. Due to their unique host-guest recognition ability and easy derivatization characteristics, they have become an important molecular building block for constructing high-performance supramolecular conjugated polymers. By covalently or non-covalently integrating macrocyclic arenes into the polymer backbone through C-H…π, π…π stacking, hydrogen bonding, and electrostatic interactions, the supramolecular polymer network based on them not only has dynamic reversibility, but also has structural stability. Conjugated polymers based on pillararenes not only retain their inherent charge conduction and photophysical properties, but also can achieve selective binding of specific ions or molecules through the host-guest recognition ability of macrocyclic arenes, thereby effectively improving energy transfer efficiency. For example, Linxian Xu et al. reported a new strategy for constructing an ALHS (artificial light-harvesting system) with a high antenna effect. This strategy self-assembles a conjugated polymer host (CPH) based on pillar[5]arene and a multi-armed guest (Gs) to construct a conjugated polymer supramolecular network (CPSN) based on pillar[5]arene. The specific binding between the host and the guest improves the donor-acceptor energy transfer ability, making it an ideal artificial light-harvesting material with excellent performance in energy transfer (A Conjugated Polymeric Supramolecular Network with Aggregation-Induced Emission Enhancement: An Efficient Light-Harvesting System with an Ultrahigh Antenna Effect / Angew. Chem. Int. Ed. 2020, 59, 9908-9913 / DOI: https: / / doi.org / 10.1002 / anie.201907678). Pillararene-based supramolecular conjugated polymers have made important progress in the fields of chemical sensing, catalysis, adsorption separation, and luminescence. However, their application in the field of electrochromism has not been reported, and further exploration of their potential functions and mechanisms is needed. However, the easy derivatization of pillararenes allows them to be introduced into conjugated polymer systems with electrochromic properties, and their unique physicochemical properties will bring new features and functions to electrochromic materials. SUMMARY
[0006] The application discloses a preparation method of a p[5]arene conjugated polymer containing a D-A-D structure.
[0007] The technical scheme adopted by the application is as follows:
[0008] The application provides a p[5]arene conjugated polymer containing a D-A-D structure, which has the following structure:
[0009]
[0010] The application further provides the preparation method of the p[5]arene conjugated polymer containing the D-A-D structure, and the specific steps are as follows:
[0011] (1) derivative of p[5]arene, including oxidation, reduction, substitution, Suzuki coupling, finally to the side chain derivative thiophene group p[5]arene, namely polymer monomer 1, the specific structure is shown in the following formula:
[0012]
[0013] (2) synthesis of the triphenylamine derivative containing the D-A-D structure, 4,4'-(benzo[1,2,5]thiadiazole-4,7-diyl)bis[N-(4-bromophenyl)-N-(p-tolyl) aniline], namely polymer monomer 2: taking 4-methyltriphenylamine as a starting material, through bromination and Suzuki coupling, the polymer monomer 2 is obtained, and the specific structure is shown in the following formula:
[0014]
[0015] (3) synthesis of the p[5]arene conjugated polymer containing the D-A-D structure, under a protective atmosphere, the polymer monomer 1, the polymer monomer 2, a catalyst and a solvent are mixed, heated to reflux, and reacted in a reflux state, so that the p[5]arene conjugated polymer containing the D-A-D structure is obtained.
[0016] Further, in the step (3), the protective atmosphere is argon.
[0017] Further, in step (3), the catalyst comprises Pd(PPh3)4, Pd(OAc)2 or Pd(PPh3)2Cl2; preferably Pd(OAc)2.
[0018] Further, in step (3), the solvent comprises N,N-dimethylacetamide or 1,4-dioxane; preferably N,N-dimethylacetamide.
[0019] Further, in step (3), the molar ratio of the side chain derived thiophene-based pillar[5]arene (polymerization monomer 1) and the triphenylamine derivative containing D-A-D structure (polymerization monomer 2) is 1-1.5:1; preferably 1.05:1.
[0020] Further, in step (3), the ratio of the amount of solvent and polymerization monomer 1 is 7 mL:0.467 mmol.
[0021] Further, in step (3), the molar ratio of the catalyst and the side chain derived thiophene-based pillar[5]arene (polymerization monomer 1) is 0.03-0.1:1; preferably 0.1:1.
[0022] Further, in step (3), the reaction temperature is 120-140℃, preferably 125-140℃; the time is 45-60 h, preferably 60 h.
[0023] Further, after the reaction is completed, the reaction mixture is extracted with dichloromethane, washed with saturated brine three times, and the organic phase is combined and dried with anhydrous Na2SO4, and the organic phase is purified by column chromatography to obtain a crude product.
[0024] Further, after obtaining the crude product, it needs to be subjected to Soxhlet extraction, and the specific operation is as follows:
[0025] Methanol, cyclohexane and chloroform are used in sequence for extraction, the chloroform extract is collected and concentrated, and then the solid product is dissolved in a small amount of tetrahydrofuran and added to a methanol solution to precipitate, and the solid product is filtered and dried.
[0026] The application also provides the use of the above-mentioned pillar[5]arene conjugated polymer containing D-A-D structure in an electrochromic device.
[0027] Further, the preparation method of the electrochromic device comprises the following steps:
[0028] (1) Preparation of electrochromic layer: mixing the pillar[5]arene conjugated polymer containing D-A-D structure and the electrolyte, dissolving with a solvent and ultrasonic shaking;
[0029] (2) The preparation of the electrochromic device: the conductive surface of the ITO conductive glass is determined by a universal meter, three narrow double-sided tapes (20*2mm) are used to form a U-shaped cavity with one thin edge of one of the ITO glasses, then another ITO glass is taken and pasted on the cavity with the conductive surface facing the cavity, the prepared electrochromic mixed solution is injected into the cavity by using a syringe, and the cavity and the periphery of the double-sided tape are packaged by using hot melt adhesive, so as to assemble an electrochromic device with a certain thickness of liquid film.
[0030] Further, in step (1), the solvent comprises tetrahydrofuran, propylene carbonate or chloroform; and the electrolyte is tetrabutylammonium perchlorate.
[0031] Further, in step (1), the ratio of the amount of the conjugated polymer to the amount of the electrolyte is 0.01mmol:0.05mmol.
[0032] Further, the electrochromic device needs to be sequentially soaked in toluene, acetone, ethanol and deionized water, and then ultrasonically cleaned and dried before use.
[0033] Compared with the prior art, the present application has the following advantages and beneficial effects:
[0034] The present application firstly applies the pillar[5]arene with a rigid macrocyclic structure to the construction of the electrochromic conjugated polymer, and introduces the D-A-D structure in the molecular design, and the technical advantages mainly embody in:
[0035] (1) The raw material of the copolymer is easy to obtain and the synthesis path is simple, and the production cost is low;
[0036] (2) The rigid macrocyclic cavity of the pillar[5]arene can improve the structural stability of the polymer and prevent the accumulation of the polymer main chains from being too close;
[0037] (3) The pillar[5]arene-based conjugated polymer not only retains its inherent charge conduction and photophysical properties, but also can realize the selective combination of the electrolyte guest molecules by means of the host-guest recognition ability of the macrocyclic arene, so as to effectively regulate the charge transfer and energy transfer efficiency;
[0038] (4) The introduction of the D-A-D structure can reduce the energy gap of the system, so that the polymer molecules can realize faster color change response and larger optical contrast at a lower voltage. BRIEF DESCRIPTION OF DRAWINGS
[0039] Figure 1 NMR spectra of the polymerized monomer 1, 2 and the D-A-D structured pillar[5]arene conjugated polymer prepared in Example 1.
[0040] Figure 2 Fluorescence titration spectrum of the host H (D-A-D structured pillar[5]arene conjugated polymer) and the guest G (tetrabutylammonium perchlorate).
[0041] Figure 3 Nonlinear regression analysis of the fluorescence titration spectrum was performed in the Scientist software to establish the host-guest binding model, and the host-guest binding mode, binding constant and residual error of the experimental data between H and G were calculated.
[0042] Figure 4 Structure diagram of the electrochromic device.
[0043] Figure 5 Transmittance change curve of the electrochromic device prepared in Example 1 of the present application under different voltages.
[0044] Figure 6 Transmittance curve of the electrochromic device prepared in Example 1 of the present application in colored state and bleached state.
[0045] Figure 7 Transmittance change curve of the electrochromic device prepared in Example 1 of the present application under about 20 cycles (step voltage is 2.4V-0V). DETAILED DESCRIPTION
[0046] In order to make the purpose, technical scheme and advantages of the present application more clear, the present application will be further described in detail below in combination with examples. It should be understood that the specific examples described herein are only used to explain the present application, and are not used to limit the present application. Those skilled in the art can modify or replace equivalently without departing from the spirit and scope of the present application, which should be covered within the protection scope of the present application.
[0047] Example 1:
[0048] 1. Synthesis process of the side chain derivative thiophene group pillar[5]arene (polymerized monomer 1):
[0049]
[0050] The synthesis of the fully-methoxylated pillar[5]arene (compound 1-1), the quinonoid pillar[5]arene (compound 1-2), the dihydroxylated pillar[5]arene (compound 1-3) and the di-OTf pillar[5]arene (compound 1-4) in the synthetic route were prepared according to the reported synthetic procedures.
[0051] Synthesis of the polymerization monomer 1: Compound 1-4 (2.87 g, 3.12 mmol), 2- thiopheneboronic acid (1.22 g, 9.39 mmol), sodium carbonate (3.3 g, 31.1 mmol) were weighed and added into a 50 mL two-necked round-bottom flask under argon atmosphere. 20 mL of 1,4-dioxane was added as solvent into the flask. Pd(PPh3)4 (180 mg, 0.156 mmol) was added into the flask. The reaction mixture was heated to 90 °C for 26 h. The reaction progress was monitored by TLC. After the reaction was completed, an appropriate amount of dichloromethane was added. The reaction mixture was extracted with 50 mL x 3 saturated brine. The dichloromethane extract was collected and dried over anhydrous sodium sulfate. The solvent was removed by evaporation. The product was separated by column chromatography using a mixture of petroleum ether, dichloromethane and ethyl acetate (V 石油醚 :V 二氯甲烷 :V 乙酸乙酯 = 25:2:1) as eluent. Finally, the white powder (polymerization monomer 1, 1.71 g) was obtained after purification. The yield was 64%.
[0052] 2. Synthesis of the triphenylamine derivative (polymerization monomer 2) containing D-A-D structure is shown in the following figure:
[0053]
[0054] (1) Synthesis of the intermediate 4,4'-(benzo[c][1,2,5]thiadiazole-4,7-diyl)bis(N-phenyl-N-(p-tolyl)benzenamine:
[0055] Compound 4-methyl-N-phenyl-N-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2- yl)phenyl)aniline (4.35 g, 11.28 mmol), 4,7-dibromobenzo[1,2,5]thiadiazole (1.325 g, 4.5 mmol), potassium carbonate (9.36 g, 67.72 mmol), were added to a 100 mL two-necked round bottom flask under argon, 20 mL of toluene and 5 mL of water were added to the reaction flask as solvent, and Pd(PPh3)4 (260 mg, 0.225 mmol) was further added. The reaction was heated to 85°C and reacted for 48 h. The reaction progress was monitored by TLC. After the reaction was completed, 50 mL x 3 of dichloromethane was added, and 50 mL x 3 of saturated brine was extracted three times. The dichloromethane phase extract was collected, dried over anhydrous sodium sulfate, and concentrated. The product was separated and purified using a chromatographic column with a mixture of petroleum ether, dichloromethane, and ethyl acetate (V 石油醚 :V 二氯甲烷 :V 乙酸乙酯 = 40:1:1) as eluent. Finally, after separation and purification, a red powder (intermediate, 1.21 g) was obtained, with a yield of 28.98%.
[0056] (2) Synthesis of polymer monomer 2, i.e., 4,4'-(benzo[1,2,5]thiadiazole-4,7-diyl)bis[N-(4- bromophenyl)-N-(p-tolyl)aniline]: The intermediate (1.15 g, 1.76 mmol) was weighed into a 50 mL two-necked round bottom flask, 15 mL of tetrahydrofuran was added under nitrogen, and the mixture was stirred until completely dissolved. NBS (0.313 g, 4.76 mmol) was dissolved in 10 mL of tetrahydrofuran solution under ice bath conditions, and was slowly added dropwise using a constant pressure dropping funnel. After the addition was completed, the reaction was allowed to proceed for 3 h, and the reaction progress was monitored by TLC. After the reaction was completed, 50 mL x 3 of dichloromethane was added, and 50 mL x 3 of saturated brine was extracted three times. The dichloromethane phase extract was collected, dried over anhydrous sodium sulfate, and concentrated. The product was separated and purified using a chromatographic column packed with silica gel of 300-400 mesh, with a mixture of petroleum ether and ethyl acetate (V 石油醚 :V 乙酸乙酯 = 50:1) as eluent. Column chromatography was performed to obtain an orange powder (polymer monomer 2, 1.38 g) with a yield of 97.3%.
[0057] Example 2
[0058] The synthesis process of the column[5]arene conjugated polymer containing a D-A-D structure is shown in the following figure:
[0059]
[0060] The side chain derivative thiophene group column [5] arene (polymerization monomer 1) (400 mg, 0.467 mmol), triphenylamine derivative containing D-A-D structure (polymerization monomer 2) (378 mg, 0.467 mmol), potassium carbonate (193.96 mg, 1.43 mmol), pivalic acid (14.33 mg, 0.14 mmol) were weighed into a 25 mL two-port round-bottom flask in turn, 7 mL of anhydrous N,N-dimethylacetamide was added under argon protection, and finally Pd(OAc)2 (7.7 mg, 0.015 mmol) was added. The reaction was refluxed at 130°C for 56 h, and the reaction progress was monitored by TLC.
[0061] After the reaction was completed, the reaction mixture was extracted with dichloromethane, washed with saturated brine three times, the organic phase was combined and dried over anhydrous Na2SO4, and flash column chromatography was performed using a mixture of dichloromethane and ethyl acetate (V 二氯甲烷 :V 乙酸乙酯 =1:1) as eluent to remove the catalyst, and a brown solid product was obtained; then Soxhlet extraction was performed using methanol, cyclohexane and chloroform in turn, the chloroform extract was collected and concentrated, and the solid product was dissolved in a small amount of tetrahydrofuran and added to a 300 mL methanol solution to precipitate it. The solid product was filtered off and dried to obtain a dark red solid powder (polymer 223 mg) with a yield of 42%.
[0062] Figure 1 The nuclear magnetic resonance hydrogen spectrum of the polymerization monomers 1 and 2 prepared in Example 1 and the column [5] arene conjugated polymer containing D-A-D structure prepared in Example 2 showed that the characteristic peaks of H at positions 2 and 5 of the thiophene ring at 6.34 ppm disappeared, and the chemical shift peaks of the conjugated polymer nuclear magnetic hydrogen spectrum were significantly broadened, indicating that the polymer was successfully synthesized.
[0063] Example 3
[0064] Optimization and screening of reaction conditions for conjugated polymers:
[0065] Using polymerization monomers 1 and 2 as reaction substrates, the factors that may affect the reaction, including reaction temperature, reaction time, catalyst dosage, and equivalent ratio between monomers, were screened and optimized by the control variable method. The reaction equation is shown in the figure below, and the specific operation steps are referred to Example 2.
[0066]
[0067] Firstly, the reaction time was kept as 45h, the molar ratio of the catalyst and polymerization monomer 1 was 0.03:1, the molar ratio of polymerization monomer 1 and polymerization monomer 2 was 1:1, and the reaction temperature was changed (120-140℃) to screen the reaction temperature. According to the experimental results, when the reaction temperature was 120℃, the reaction yield was 21%, and when the temperature was increased to 140℃, the yield was 35%, so the reaction temperature was preferably 140℃;
[0068] Similarly, according to the operation steps described in Example 2, the reaction time, the amount of catalyst, and the equivalent ratio between monomers were screened and optimized by using the above control variable method, and the main results are shown in Table 1.
[0069] Table 1 Screening of reaction conditions
[0070]
[0071] According to the results in Table 1, it can be concluded that in the process of synthesizing conjugated polymers, the reaction temperature is preferably 140℃, the reaction time is preferably 60h, the molar ratio of the catalyst and polymerization monomer 1 is preferably 0.1:1, and the molar ratio of polymerization monomer 1 and polymerization monomer 2 is preferably 1.05:1.
[0072] Test Example 1
[0073] A fluorescence titration experiment was performed on the host H (a column [5] arene conjugated polymer containing a D-A-D structure) and the guest G (tetrabutylammonium perchlorate). The experiment was performed using a microsyringe method, and the specific operation process was as follows: 4.262mg of host H (a column [5] arene conjugated polymer containing a D-A-D structure) was weighed into a 5mL volumetric flask, THF (tetrahydrofuran) was added, and the volume was adjusted and shaken to obtain a mother liquor; 40μL of the mother liquor was taken with a microsyringe and added to a cuvette, 2mL of THF was added, the glass stopper of the cuvette was covered, and the mixture was shaken; the concentration of the host solution was kept at 20μmol / L, and the guest G (tetrabutylammonium perchlorate) was gradually added to the cuvette containing the host H (a column [5] arene conjugated polymer containing a D-A-D structure) using a microsyringe, and the change in the concentration of the guest in the cuvette was controlled by controlling the volume of the guest solution added. After the addition was completed, the glass stopper of the cuvette was covered again, the cuvette was shaken to mix the solution thoroughly, and the fluorescence emission spectrum was collected under excitation at 294nm (corresponding to the maximum absorption wavelength of the host molecule) at 18℃ for 5min.
[0074] Data extraction adopts half-peak integral method, and the corresponding value is calculated according to the formula: ΔI=(I-I0) / I0. Four groups of parallel samples are set in all experiments, and the arithmetic average value of ΔI is calculated to improve the data reliability. Finally, the concentration and the arithmetic average value of ΔI are imported into Scientist 3.0 software for non-linear regression analysis to establish the host-guest binding model. Figure 2 It can be seen from the above table that the fluorescence of the host H is gradually quenched and then stabilized with the addition of the guest G (0 mmol / L, 0.1 mmol / L and 1 mmol / L). Figure 3 Scientist software is used to perform non-linear regression analysis on the fluorescence titration spectrum to establish the host-guest binding model, calculate the host-guest binding mode, binding constant and experimental data residual error between H and G. According to the fitting results, it can be confirmed that the 1:1 binding model is consistent between H and G, the binding constant K= (23.252 formula, binding constant and experimental data. It is speculated that when the two are combined in a 1:1 ratio, due to the close spatial distance between the nitrogen cation and the polymer main chain after combination, a charged ion is introduced on the polymer, and this embedded positive center can improve the conductivity of the polymer main chain itself.
[0075] Example 4
[0076] A preparation method of an electrochromic device, comprising the following steps:
[0077] (1) Preparation of electrochromic layer: 0.01 mmol of column [5] arene conjugated polymer and 0.05 mmol of electrolyte (tetrabutylammonium perchlorate) are weighed in a 1 mL sample bottle, and then dissolved in 0.5 mL of solvent (tetrahydrofuran) and ultrasonically shaken;
[0078] (2) Preparation of electrochromic device: the conductive surface of the ITO conductive glass is determined by a multimeter, and three narrow double-sided tapes (20x2 mm) are used to form a U-shaped cavity with one narrow edge of the glass. Then, another ITO glass is taken, and the conductive surface is placed in the cavity and is placed in the cavity. Then, a syringe is used to inject the prepared electrochromic mixed solution into the cavity, and then hot melt adhesive is used to package the cavity and the surrounding double-sided tape to assemble an electrochromic device with a certain thickness of liquid film. The structure is shown in Figure 4 .
[0079] Test Example 2
[0080] The electrochromic device with the column [5] arene conjugated polymer as the electrochromic active layer is prepared according to the preparation method of the electrochromic device. Figure 5 It can be seen from the formula (I) that the color of the polymer does not change obviously under the voltage below 0.8V, and the transmittance also does not change obviously. It is possible that the oxidation process of the polymer does not occur under the voltage; when the voltage is further increased to 2.1V, the oxidation potential is reached, the polymer is oxidized, and the color changes from yellow to dark green.
[0081] Under the same test condition, the voltage is continuously increased to 3V, it is found that the color of the device in the oxidation state is further deepened, and the transmittance change of the polymer device in the coloring state and the bleaching state is obtained, as shown in the formula (II), the optical contrast of the polymer at 784nm reaches 53.12%, and the optical contrast is large. Figure 6
[0082] Meanwhile, the cycle stability of the device is determined, the step voltage of 0V-2.4V is applied to the device by using the electrochromic cycle tester and the ultraviolet-visible spectrophotometer, about 20 cycle periods are carried out, and the transmittance change curve is determined, and the result is shown in the formula (III). Figure 7 It can be seen from the formula (III) that after about 20 cycle periods, the optical contrast of the polymer device still maintains 69.2% of the initial optical contrast, and the cycle stability is good. Figure 7
[0083] Compared with the prior art, the present application has the following advantages and beneficial effects:
[0084] The column [5] arene with a rigid macrocyclic structure is applied to the construction of the electrochromic conjugated polymer for the first time in the present application, and the D-A-D structure is introduced in the molecular design, and the technical advantages mainly embody in that:
[0085] (1) The raw material of the copolymer is easy to obtain, the synthesis path is simple, and the production cost is low;
[0086] (2) The rigid macrocyclic cavity of the column [5] arene can improve the structural stability of the polymer and prevent the accumulation of the polymer main chains from being too close;
[0087] (3) The column [5] arene-based conjugated polymer not only retains the inherent charge conduction and photo-physical properties, but also can realize the selective combination of the electrolyte guest molecules by means of the host-guest recognition ability of the macrocyclic arene, so as to effectively control the charge transfer and energy transfer efficiency;
[0088] (4) The introduction of D-A-D structure can reduce the energy gap of the system, so that the polymer molecules can achieve faster color change response and greater optical contrast at lower voltage. Specifically, compared with the prior art PEDOT:PSS material, the response is slow (both bleaching and coloring require several seconds or even tens of seconds), and the optical contrast is low (less than 30%), while the color change response time and the bleaching response time of the color change device prepared by the present application are 1.25 s and 2.26 s respectively, and the optical contrast is also improved to 53.12% (at 784 nm).
Claims
1. A pillar[5]arene conjugated polymer containing a D-A-D structure, characterized in that, has the following specific structure:
2. A method for preparing the column[5]arene conjugated polymer containing D-A-D structure according to claim 1, characterized by, comprises the following steps: (1) Derivatization of pillar[5]arene, including oxidation, reduction, substitution, Suzuki coupling, and finally to the side chain derivative of thiophene group of pillar[5]arene, i.e. polymer monomer 1, the specific structure is shown as follows: (2), 4-methyltriphenylamine as starting material, through bromination, Suzuki coupling, to obtain a triphenylamine derivative containing D-A-D structure, 4,4'-(benzo[1,2,5]thiadiazole-4,7-diyl)bis[N-(4-bromophenyl)-N-(p-tolyl) aniline], i.e. polymer monomer 2, the specific structure is shown as follows: (3) Synthesis of pillar[5]arene conjugated polymer containing D-A-D structure, mixing polymer monomer 1, polymer monomer 2, catalyst and solvent under protective atmosphere, heating to reflux, and carrying out reaction under reflux, to obtain pillar[5]arene conjugated polymer containing D-A-D structure.
3. The method according to claim 2, wherein the method for preparing a D-A-D structured column [5] arene-conjugated polymer is characterized by, In step (3), the protective atmosphere is argon; the catalyst comprises Pd(PPh3)4, Pd(OAc)2 or Pd(PPh3)2Cl2; and the solvent comprises 1,4-dioxane or N,N-dimethylacetamide.
4. The method according to claim 2, wherein the method for preparing a D-A-D structured column [5] arene-conjugated polymer is characterized by, In step (3), the molar ratio of polymer monomer 1 and polymer monomer 2 is 1-1.5:1; the ratio of the amount of solvent to polymer monomer 1 is 7 mL:0.467 mmol; and the molar ratio of catalyst to polymer monomer 1 is 0.03-0.1:
1.
5. The method according to claim 2, wherein the method for preparing a D-A-D structured pillar[5]arene conjugated polymer is characterized by, In step (3), the reaction temperature is 120-140℃, and the time is 45-60 h.
6. Use of a pillar[5]arene conjugated polymer containing D-A-D structure according to claim 1 in an electrochromic device.
7. Use according to claim 6, characterized in that, The preparation method of the electrochromic device comprises the following steps: (1) Preparation of electrochromic layer: mixing pillar[5]arene conjugated polymer containing D-A-D structure and electrolyte, dissolving with a solvent and shaking uniformly under ultrasonic; (2) Production of electrochromic device: simple assembly is adopted for assembly, the conductive surface of ITO conductive glass is determined by using a multimeter, three narrow double-sided tapes are used to form a U-shaped cavity with one narrow edge of the glass, then another ITO glass is taken, the conductive surface is placed in the cavity and is misaligned with the cavity, a prepared electrochromic mixed solution is injected into the cavity by using a syringe, and the cavity and the periphery of the double-sided tape are packaged by using hot melt adhesive, to assemble an electrochromic device with a certain thickness of liquid film.
8. Use according to claim 7, characterized in that, In step (1), the solvent comprises tetrahydrofuran, propylene carbonate or chloroform; and the electrolyte is tetrabutylammonium perchlorate.
9. Use according to claim 7, characterized in that, In step (1), the ratio of the amount of conjugated polymer to electrolyte is 0.01 mmol:0.05 mmol.
10. Use according to claim 7, characterized in that, The electrochromic device needs to be sequentially soaked in toluene, acetone, ethanol and deionized water, cleaned under ultrasonic and dried before use.